Study on Evaluation Models of Hidden Curriculum: Illuminative, Case Study and Responsive - Wathani, Diki Hasrul; Arifin, Zainal (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
The purpose of this research is to explore and evaluate the influence of the hidden curriculum on character development among students in a formal educational setting. The background of this study stems from the observation that many essential aspects of education are not covered in the formal curriculum, necessitating further attention in evaluation. The urgency of this research lies in the need to understand the dynamics of the hidden curriculum, which can impact students"™ behavior, attitudes, and values, thereby contributing to their character development. The research method used is a qualitative approach with an illuminative evaluation model, involving three stages: curriculum document investigation, classroom observation, and interviews with teachers and students. Collected data were analyzed to identify emerging patterns and themes related to the hidden curriculum. The findings indicate that the hidden curriculum has a significant impact, both positive and negative, on students"™ learning experiences. The study reveals that the interaction between the intended and learned curriculum creates space for the internalization of certain behaviors and attitudes that either support or hinder educational goals.The conclusion of this study emphasizes the importance of awareness of the hidden curriculum in curriculum development and teaching practices. By understanding and evaluating the hidden curriculum, educators can design more holistic and effective learning experiences that focus not only on academic achievement but also on students"™ character formation. This research can serve as a reference for curriculum developers and educators in creating a better learning environment.